KEWENANGAN PROVOS BRIMOB POLRI TERHADAP PELANGGARAN DISIPLIN ANGGOTA (STUDI PERATURAN PEMERINTAH NOMOR 2 TAHUN 2003 TENTANG PERATURAN DISIPLIN ANGGOTA KEPOLISIAN NEGARA REPUBLIK INDONESIA): STUDI PERATURAN PEMERINTAH NOMOR 2 TAHUN 2003 TENTANG PERATURAN DISIPLIN ANGGOTA KEPOLISIAN NEGARA REPUBLIK INDONESIA - Faharudin Faharudin; Hidayat Sandra (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The rapid development of society, accompanied by the emergence of the principles of the rule of law, human rights, globalization, democratization, decentralization, transparency, and accountability, has given rise to new paradigms in understanding the objectives, duties, functions, authorities, and responsibilities of the Indonesian National Police. This condition has also increased public demands and expectations regarding the performance of the Indonesian National Police, which is increasingly oriented toward serving the interests of the community. The study methodology selected was normative legal research (normative law). Based on the scientific logic of jurisprudence, normative legal research is a scientific research methodology that seeks to discover the truth from a normative standpoint. The legislative approach is used to answer the research issue by analyzing a number of laws and regulations that are pertinent to its main focus. Additionally, the conceptual approach is used to examine the concept of disciplinary punishment as well as disciplinary hearings when police personnel violate service regulations. According to research, the National Police of the Republic of Indonesia's ability to successfully carry out its responsibilities, which include upholding public safety and order, enforcing the law, and protecting, assisting, and serving the populace, depends not only on the caliber of police officers' expertise and professional abilities but also on each member of the force acting honorably in society. Every member of the National Police must always have a thorough understanding of police professional ethics, embody its spirit, and demonstrate this in their attitude and behavior while performing their duties and using their authority in order to achieve such conduct; in this way, they must avoid dishonorable behavior and the abuse of authority.